Promosi Produk Footwear di Instagram - Mila Salsabila; Anne Ratnasari (UNISBA Press, 2022)
Abstract. The development of social media has made online shopping the most promising business with significant developments. Dianable is a brand that has developed through social media Instagram, a brand of women's sandals and shoes that has uniqueness and characteristics in terms of design, material, color, and fashion concept. Dianable's promotions take full advantage of current social media, especially Instagram. As the main media, Instagram is very effective for sharing information about the Dianable brand and products. This research is entitled “Footwear Product Promotion on Instagram” (a case study on the @Dianable_ account). The purpose of this study is to find out what promotions are used in the @dianable_ instagram account, understand the Instagram features used by Dianable, find out why Dianable held a surprise giveaway to build consumer loyalty. The research method used is a qualitative research method with a case study approach. Data collection techniques are carried out by; interviews, observations, literature studies, documentation. Informants in this study were Owner and Digital Marketing officer Dianable. This research shows that Dianable in its promotion uses three elements of promotion including advertising (periklanan), sales promotion (promosi penjualan), and public relations (hubungan masyarakat). Dianable also takes advantage of Instagram features such as feeds, stories, live and Instagram shopping. As well as packaging a surprise giveaway as a form of appreciation to consumers who have collected Dianable products, this is done with the aim of increasing loyalty in order to create trust, repeat purchases and make recommendations to other potential customers. Abstrak. Berkembangnya media sosial membuat online shop menjadi bisnis paling menjanjikan dengan perkembangan yang signifikan. Dianable menjadi salah satu brand yang berkembang melalui media sosial instagram, salah satu brand sandal dan sepatu wanita yang memiliki keunikan dan ciri khas dari segi design, material, warna, hingga konsep fashion. Promosi yang dilakukan Dianable sangat memanfaatkan media sosial saat ini, terutama instagram. Sebagai media utama, instagram sangat efektif untuk membagikan informasi mengenai brand dan produk Dianable. Penelitian ini berjudul “Promosi Produk Footwear di Instagram” (studi kasus pada akun @Dianable_). Tujuan penelitian ini untuk mengetahui promosi apa saja yang digunakan dalam akun instagram @dianable_, memahami fitur-fitur instagram yang dimanfaatkan Dianable, mengetahui alasan Dianable mengadakan surprise giveaway untuk membangun loyalitas konsumen. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan dengan cara; wawancara, observasi, studi pustaka, dokumentasi. Informan dalam penelitian ini adalah Owner dan Digital Marketing officer Dianable. Penelitian ini menghasilkan bahwa Dianable dalam promosinya menggunakan tiga elemen bentuk promosi diantaranya iklan, sales promotion (promosi penjualan), dan public relation (hubungan masyarakat). Dianable juga memanfaatkan fitu instagram seperti feeds, story, live dan instagram shopping. Serta pengemasan surprise giveaway sebagai bentuk apresiasi kepada konsumen yang sudah mengkoleksi produk Dianable, hal ini dilakukan dengan tujuan meningkatkan loyalitas agar menciptakan kepercayaan, pembelian yang berulang dan adanya perekomendasian kepada calon konsumen lain.